A Comparison of Within- and Across-Subject Analysis of the Expectancy-Valence Model For Predicting Effort - Muchinsky, Paul M. (Academy of Management Journal, 1977)
The article discusses a study which compared the validity of within and across subjects analyses in predicting job effort. The validity coefficients of the complete model and components varied greatly both within and between individual subjects. The best predictor of self-report effort was a single component of the model. Analysts say the weakest part of the study is that the criterion is not a behavioral measure. The valences, instrumentalities, and expectancies are related to the criterion of a self-report rating of effort.